Monday

April 21, 2014

April 21, 2014

Posted by **Anonymous** on Tuesday, January 21, 2014 at 1:47pm.

a. (81a^4c^3)/(b^2)

b. (81a^4)/(b^2c^3)

c. (3a^4)/(b^2c^3)

d. (3a^4c^3)/(b^2)

D

What is -a^-2 if a = -5?

a. -25

b. 25

c. -1/25

d. 1/25

D

What is (-m)^-3n if m = 2 and n = -24?

a. 3

b. -3

c. 4

d. -4

A

- Algebra Check -
**Damon**, Tuesday, January 21, 2014 at 2:31pmWhat is the simplified form of 3a^4b^-2c^3?

a. (81a^4c^3)/(b^2)

b. (81a^4)/(b^2c^3)

c. (3a^4)/(b^2c^3)

d. (3a^4c^3)/(b^2)

D YES

What is -a^-2 if a = -5?

a. -25

b. 25

c. -1/25

d. 1/25

D No -1/(-5)^2 = -1/25 so C

What is (-m)^-3n if m = 2 and n = -24?

a. 3

b. -3

c. 4

d. -4

A NONE OF THESE. -2^72 is huge. You have a TYPO

- Algebra Check -
**Anonymous**, Tuesday, January 21, 2014 at 2:37pmIt is not -3n. It is (-m)^-3 n. So it would be -.125* -24, which is how I did it.

- Algebra Check -
**Damon**, Tuesday, January 21, 2014 at 2:41pm[(-m)^-3 ] n

[1/(-2)^3] (-24)

(1/-8)(-24)

3

YES A

- Algebra Check -
**Anonymous**, Tuesday, January 21, 2014 at 2:54pmThank you so much! Just one quick question...is it a rule to always simplify first and then substitute, as in question 2?

- Algebra Check -
**Damon**, Tuesday, January 21, 2014 at 3:42pmThat is up to you.

**Related Questions**

math binomial expansion - binomial expansion (3a^2-2b^3)^4 is this right? (3a^2...

math - 24b^4c^3 / 6b^2c A) 3b^2c^2 B) 4b^4c^2 C) 4b^3c^2 D) 4b^2c^2 E) 3b^4c^3

Math - Hi, I need a little help with solving this question for c: (2c-1)^3=4c^2-...

algebra - 1 Solve the set of linear equations by the matrix method : a+3b+2c=3...

maths - (Q1)a+3b+2c=3,2a-b-3c=-8,5a+2b+c=9.solve for a,b&c by matrix method. (a)...

More Math To Check Please - 4c^2 - 12c + 9 This is what I got: (2c+3)(2c-3) *Is ...

algebra - (6a^3bc^5)(-3a^4b^2c^3) simplify

MATH Matrix Equation - If 4a + 3b + c = 27 3a + b + 4c = 16 9a + 2b + 3c = 33 ...

Math Matrix EQ - If 4a + 3b + c = 27 3a + b + 4c = 16 9a + 2b + 3c = 33 then 2a...

algebra - Given f(x) = 2x - 5, find f(-3a). F(x)= 2(-3a) -5 F(-3a) = 2(3a)-5 = 1...